2020
DOI: 10.21037/acs-2019-surd-172
|View full text |Cite
|
Sign up to set email alerts
|

Right anterior mini-thoracotomy and sutureless valves: the perfect marriage

Abstract: Background: A minimally invasive approach (MIA) reduces mortality and morbidity in patients referred for aortic valve replacement (AVR). Sutureless technology facilitates a MIA. We describe our experience with the sutureless Perceval (LivaNova, Italy) aortic bioprosthesis through a right anterior mini-thoracotomy (RAMT) approach. Methods: Between March 2011 and October 2019, 1,049 patients underwent AVR with Perceval bioprosthesis. Five hundred and three patients (48%) were operated through a RAMT approach in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
(25 reference statements)
1
27
0
1
Order By: Relevance
“…Surgical aortic valve replacement (SAVR) with the sutureless self-expanding Perceval aortic bioprosthesis (LivaNova Group, Milan, Italy) was developed to combine the advantages of the transcatheter aortic valve replacement (TAVR) procedure, allowing for a fast implantation with no need for suturing, with the benefits of a conventional surgical approach owing to the possibility of removing the native valve along with the calcifications. The valve has grown in popularity mostly due to the reduced cardiopulmonary bypass (CPB) time ( 1 ), the improved myocardial recovery time and its application in minimally invasive cardiac surgery (MICS) procedures ( 2 ). In addition, the three PARTNER clinical trials' ( 3 5 ), the SURTAVI trial ( 6 ) and other observational cohort studies ( 7 , 8 ) have evidenced the non-inferiority of TAVR vs. SAVR.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical aortic valve replacement (SAVR) with the sutureless self-expanding Perceval aortic bioprosthesis (LivaNova Group, Milan, Italy) was developed to combine the advantages of the transcatheter aortic valve replacement (TAVR) procedure, allowing for a fast implantation with no need for suturing, with the benefits of a conventional surgical approach owing to the possibility of removing the native valve along with the calcifications. The valve has grown in popularity mostly due to the reduced cardiopulmonary bypass (CPB) time ( 1 ), the improved myocardial recovery time and its application in minimally invasive cardiac surgery (MICS) procedures ( 2 ). In addition, the three PARTNER clinical trials' ( 3 5 ), the SURTAVI trial ( 6 ) and other observational cohort studies ( 7 , 8 ) have evidenced the non-inferiority of TAVR vs. SAVR.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when compared to surgical AVR, these devices also allow for shorter CPB and cross-clamp times (4,5). However, SBs and RDBs provide clear-cut advantages beyond the reduction of operative times, such as improved hemodynamic performance and the facilitation of mini-invasive approaches, which renders these devices competitive in specific cases, as well as in comparison with TAVI [ 3 , 6 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that RAMT AVR is associated with a low rate of postoperative complications and favorable midterm survival 19,23,24,36–46 . Our center established a minimally invasive surgical program dedicated to the sternum‐sparing RAMT approach in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Operative setup for the right anterior minithoracotomy (RAMT) approach. (B) Exposure of the aortic valve through a RAMT Various studies have shown that RAMT AVR is associated with a low rate of postoperative complications and favorable midterm survival 19,23,24,[36][37][38][39][40][41][42][43][44][45][46]. Our center established a minimally invasive…”
mentioning
confidence: 99%